Trastuzumab-deruxtecan: an investigational agent for the treatment of HER2-positive breast cancer. (1st September 2020) - Bartsch, Rupert
ABSTRACT: Introduction: The prognosis of patients with HER2-positive breast cancer was dramatically changed by the introduction of targeted therapies. With trastuzumab, pertuzumab, and T-DM1 widely used as (neo)adjuvant therapy today, novel treatment options are required to optimize treatment of HER2-positive metastatic disease. Trastuzumab-deruxtecan is an antibody-drug conjugate (ADC) consisting of a monoclonal humanized immunoglobulin G1 antibody, a linker molecule, and the exatecan derivative DXd. T-DXd has a higher drug to antibody ratio compared with T-DM1; in addition, membrane permeability of DXd is high, resulting in an increased bystander effect. Results from early clinical development suggest a clinically relevant activity of T-DXd in heavily pretreated patients with HER2-positive metastatic breast cancer progressing on T-DM1. Interstitial lung disease was a side-effect requiring special attention and was observed in approximately 13% of patients. Areas covered: This article reviews preclinical and clinical data on T-DXd. A systematic literature search was performed to identify relevant publications. The search included original research articles, abstracts from major conferences, and reviews and was limited to English-language publications. Expert opinion: T-DXd is an efficacious and tolerable drug and harbors promise as a key addition to the therapeutic field in HER2-positive breast cancer.